Bigger than life : the close-up and scale in the cinema - Doane, Mary Ann (Duke University Press, 2021)
"Mary Ann Doane examines how the scalar operations of cinema, especially those of the close-up, disturb and reconfigure the spectator's sense of place, space, and orientation."--